Bidang Minat Karir Peserta Didik Sebelum dan Setelah Pandami Covid-19 Di SMA Kr.2 Binaan Khusus Tomohon - Kauanng, sinta Elisa Jelita; Narosaputra, Dewo Agung Nugroho; Wantah, Mario Erick (Jurnal Ilmiah Mandala Education (JIME), 2023)
The Ministry of Education and Culture has implemented a policy to study and work from home since March 2020. Mas Minister (nickname for the Minister of Education and Culture of the Republic of Indonesia) implemented the Study From Home policy as a bridge or preparation for a new normal era. Whereas in early March 2022 President Joko Widodo officially ended the PSBB or Large-Scale Social Restrictions in Indonesia. This research attempts to provide an overview of the differences in the career interest areas of Class X Students before the Covid-19 Pandemic in 2019 and after the Covid-19 Pandemic in 2022. The sample in this study was Class X Students who took part in the Participant Admission Selection New students in one of the Leading Schools in Tomohon City, North Sulawesi, namely at SMA Kr.2 Special Assistance Tomohon. This school requires all of its students to live in dormitories and requires students to have academic and personality advantages, including an IQ score that is more than the High Average or above average. So that a sample of 75 people was obtained consisting of 55 students before the pandemic and 20 students after the pandemic who met the criteria needed in this study. Meanwhile, there was a significant difference in the results, namely that as many as 45% of class X students before the pandemic preferred work related to personal-social, namely work related to personal service, teaching and work that required social skills. Not only that, class X students who entered in 2019 liked the type of job interest that required routine and creative hand skills with a contribution of 50.9%. Whereas in class X students who will enter in 2022, as much as 40% prefer work related to the fields of mechanics & arts, which involve a lot of skills in understanding numbers and symbols or also called computational as much as 50%, so that the type of work that is of greater interest leading to independent work, entrepreneurship or jobs that offer services in the field of digital art as well as jobs that involve assembly and machining skills, both in the form of hard wear and softwear machining.